The Pelatihan Pengelolaan Keuangan dan Pemasaran Produk Pada Destinasi Wisata Kampung Caping Kota Pontianak: KAMPUNG CAPING TOURISM DESTINATION PONTIANAK CITY'S PRODUCT MARKETING AND FINANCIAL MANAGEMENT TRAINING - Fiorintari, Fiorintari; Widodo, Agus; Cahyowati, Anik; Wana, Desty; Lestari, Melati Pramudita; Triani, Merry; Rukmi, Murti Puspita; Indriani, Ika Kurnia; Sari, Wida Arindya; Nugroho, Yohanes Adi (Kapuas, 2023)
The implementation of community service aims to provide training and empower the community regarding the importance of financial management and awareness of the potential of tourist villages. This community service activity is carried out by providing material on simple financial management based on SAK EMKM, and providing an understanding that people can realize and make their living environment a tourist destination. The results of this activity the participants were able and able to compile simple financial reports based on SAK ETAP and were able to describe what potentials exist in the Caping Tourism Village, Pontianak City.